Neurolinguistic Programming in EFL Classrooms: Enhancing Engagement and Language Acquisition - MASITA, Asia (Politeknik Negeri Ujung Pandang, 2025)
This study investigates the impact of Neuro-Linguistic Programming (NLP) techniques on student engagement and language proficiency in English as a Foreign Language (EFL) classroom. Adopting a mixed-methods approach, the research involved sixty EFL students from a private language school. Quantitative data were collected through pre- and post-intervention surveys and standardized language proficiency tests, revealing a 25% increase in student engagement and a 15% improvement in language proficiency scores. Additionally, qualitative data from bi-weekly classroom observations highlighted enhanced classroom dynamics, increased student confidence, and reduced language anxiety. The findings highlight the potential of specific NLP techniques, such as anchoring positive emotions and reframing challenges, in creating a more supportive and effective learning environment. These results contribute to the discourse on innovative teaching methodologies, suggesting that NLP can significantly enhance EFL teaching strategies and improve student outcomes.